(De)confined notes. On the contributions of intersectionality to the challenges of Covid 19 - de los Reyes, Paulina (Critical Proposals in Social Work, 2021)
This article interrogates how intersectional perspectives can contribute to a deeper understanding of the operations of power in a context of sanitary crisis while delivering a reflection on the theoretical premises and political potential of these perspectives in the historical situation we are experiencing. The central argument is that intersectional approaches not only help us understand the differentiating impact of sanitary measures on the structural inequalities that construct the social order, but also allow us to identify how this order can be transgressed, resisted and negotiated in a crisis situation.